The Impact of Online Learning Implementation on Student’s Learning Outcomes in Al Quran Memorization - Kurniawati Hasjanah; Novianto B Kurniawan; Tiodora H Siagian (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2022)
The spread of the coronavirus changes all human activities, including in the education system. The learning process was conducted at home through an online system based on the distance learning policy, in accordance with a circular issued by the Minister of Education and Culture on 24 March 2020. Unfortunately, the online system has challenges in the learning process because its impacts the allocation of time for Al Quran memorization at SD Muhammadiyah East Jakarta. This study focused to find the impact of online learning on students' learning outcomes in Al Quran memorization and the significant variable that impacts learning outcomes in Al Quran memorization. This study used a quantitative. The data collection technique is the survey. The subject of the studies includes students in sixth grade at SD Muhammadiyah East Jakarta. The analysis technique used multiple regression analysis with an error rate of 5%. The result of this study stated there is a significant impact of online learning implementation on the student’s learning outcomes of Al Quran memorization which is inferred from significance was 0,00 < 0,05 then H1 was accepted. It means there is a significant impact on communication, resources, disposition, and bureaucratic structure on learning outcomes of Al Quran memorization. Moreover, communication was an essential variable that would impact online learning.